Analisa Asuhan Keperawatan pada Pasien dengan CHF menggunakan posisi semifowler untuk meningkatkan Saturasi Oksigen - Tantri Puspita; Rangga Prayoga; Yusup Mulyana; Sri Yekti Widadi (Ruang Ide, 2022)
Background: Cardiovascular disease is a health problem in both developed and developing countries. One of the most common cardiovascular diseases in Indonesia is congestive heart failure. Congestive heart failure is a condition in which the heart is unable to maintain adequate cardiac output to meet metabolic and tissue oxygen demands despite good venous flow. Objective: This case study aims to obtain an overview of applying semi-fowler position to increase oxygen saturation in patients with congestive heart failure. Methods: The method used was a descriptive case study by conducting nursing care and literature review. Participants in this study were patients with congestive heart failure with impaired breathing patterns. Result: This case showed that applying semi-fowler position to Cardiac Heart Failure Patient was increased the oxygen saturation, which is characterized by a significant increase in oxygen saturation value with an average value of 3% each day. Conclusion: nurse can help patient increasing the oxygen saturation on CHF patient using semi fowlers position. Keywords:Nursing Care, Heart Failure, semi-fowlers